Water and the Cell - Pollack, Gerald H.; Cameron, Ivan L.; Wheatley, Denys N.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book deals with the role of water in cell function. Though long recognized to be central to cell function, water's role has not received the attention lately that it deserves. This book brings the role of water front and central. It presents the most recent work of the leading authorities on the subject, culminating in a series of sometimes astonishing observations. Water is a subject of interest to virtually everyone. It is becoming increasingly important in health therapy, in the environment, in chemistry and physics, and certainly in cells. Thus, this groundbreaking volume will be of great interest to a broad audience, well beyond those in biology alone. The reader will be richly awarded with insights difficult or impossible to obtain in current textbooks, which generally treat water merely as a background carrier with limited significance.
A Convergence of Experimental and Theoretical Breakthroughs Affirms the PM theory of Dynamically Structured Cell Water on the Theory's 40th Birthday -- Molecular Basis of Articular Disk Biomechanics: Fluid Flow and Water Content in the Temporomandibular Disk as Related to Distribution of Sulfur -- Coherent domains in the streaming cytoplasm of a giant algal cell -- The glassy state of water: A 'stop and go' device for biological processes -- Information Exchange within Intracellular Water -- Biology's Unique Phase Transition Drives Cell Function -- The Effects of Static Magnetic Fields, Low Frequency Electromagnetic Fields and Mechanical Vibration on some Physicochemical Properties of Water -- Solute Exclusion and Potential Distribution Near Hydrophilic Surfaces -- Vicinal Hydration of Biopolymers: Cell Biological Consequences -- The Liquid Crystalline Organism and Biological Water -- The Unfolded Protein State Revisited -- Some Properties of Interfacial Water: Determinants for Cell Architecture and Function? -- Donnan Potential in Hydrogels of Poly(Methacrylic Acid) and its Potassium Salt -- Biological Significance of Active Oxygen-Dependent Processes in Aqueous Systems -- The Comprehensive Experimental Research on the Autothixotropy of Water -- Non-Bulk-Like Water on Cellular Interfaces -- The physical nature of the biological signal, a puzzling phenomenon: the critical contribution of Jacques Benveniste -- Freezing, Flow and Proton NMR Properties of Water Compartments in the Temporomandibular Disc.
Keywords: LIFE SCIENCES; HUMAN PHYSIOLOGY; CYTOLOGY; FLUIDS; SURFACES (PHYSICS).; LIFE SCIENCES; CELL BIOLOGY; HUMAN PHYSIOLOGY; SURFACES AND INTERFACES, THIN FILMS; FLUIDS